Production of Biodegradable Bioplastic from Industrial and Agricultural Waste - Rasheeda Khanam (Current Advances in Geography, Environment and Earth Sciences Vol. 9, 2022)
Ghee residue is the dark, mass-like residue received after the clarified butter is extracted via way of means of heating the butter. Much of this ghee residue is often received in all dairies. The residue has no similar use and is dumped withinside the agricultural field. However, the Ghee residue incorporates many phenolics and, for this reason, can be used as a supply of carbon and nitrogen in specific ways. The modern-day invention relates to bioplastics from the waste received from dairy industries and agriculture. This progressive bioplastic is appropriate for dry meal packaging. The present invention has been examined for its tensile energy via electromechanical equipment. It is reported to have tensile energy of 41.539 MPa and 29.031 MPa, for the bioplastic produced from agricultural waste-Raw Banana peel and dairy waste-Molten butter extract, respectively. Similarly, the elongation percentage becomes measured as 104% and 218%, respectively. Its migration test using n-heptane as a stimulant for 30 minutes at \(38^°\)C becomes stated as 0.6 mg/dm2 (Industrial waste) and 0.5 mg/dm2 (Agricultural waste). The presence of phenolic compounds is effective in preserving the packed meals secure with a very low migration degree compared to the synthetic polymers. It is easily biodegradable in water (<24 hours) and in soil (20-30 days approximately). After biodegradation, it can act as a bio-fertilizer in fields for growing plants.